SISTEM INFORMASI SURAT TUGAS BERBASIS WEBSITE PADA KANTOR KEMENTRIAN AGAMA KABUPATEN BOGOR - Murdika Wahyuda, (2022)
The letter system currentlyyplays a very importanttrole in the sustainabilityyof the organization, namely as assource offinformation anddthe center ofmmemory for annorganization, one of which is the Officeeof the Ministryoof Religion offBogor Regencywwhich currentlyyuses annassignment letter system that has not been omputerized, soothat in makinggassignments it is nottyet efficient. Therefore, a structured website-baseddassignment letter system is needed to facilitate employee performance in managinggassignmentswwith an Assignment Letter Information System application. This applicationnis baseddon a website designed using the PHP programming languageeand MySQLldatabase. In this study, the researcher used a qualitative approach by ollectingiinformationnthrough observation, interviews, andlliterature studiesaand analyzinggthe data. To supporttthis research, the author uses the SDCL (System Development Life Cyle) system development method because it is suitable for use in the scope discussed by the author.